Peningkatan Hasil Belajar IPA Melalui Model Pembelajaran Think-Talk-Write Bervariasi Pada Siswa Kelas VIII A SMPS Muhammadiyah Ende - Rosminta (Ekspektasi: Jurnal Pendidikan Ekonomi, 2022)
This study aims to improve learning outcomes, interest, motivation, and activeness, creativity and collaboration in learning science on the material: the Growth and Development of organism. The results show that 1) student achievement results have increased from the initial conditions to the end of the first cycle conditions and continued to cycle II there was an increase as follows: for the highest value of 80 it increased to 90 in cycle I, and increased again to 95 in cycle II. For the lowest value of 50 it rose to 75 in cycle I, and rose again to 76 in cycle II, for the average value of 66.19 in the pre-cycle rose to 81.34 in the first cycle, and rose again to 87.16 in the second cycle, 14 students completed (43.75%) increased in the first cycle to 36 students (100%), and in cycle II, for students who have not finished as many as 21 students, it drops to 0 students in cycle I and cycle II.